PENGARUH INTEGRITAS MAHASISWA, MOTIVASI BELAJAR, PEMAHAMAN AKUNTANSI DAN PENYALAHGUNAAN TEKNOLOGI INFORMASI TERHADAP PERILAKU KECURANGAN AKADEMIK (Studi Empiris Pada Mahasiswa Universitas Islam Malang dan Universitas Islam Madura) - Dwi Shindi Syafriyanti; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of Student Integrity, Learning Motivation, Accounting Understanding and Misuse of Information Technology on Academic Fraud Behavior. The population in this study were students of the Accounting Study Program of the Islamic University of Malang and the Islamic University of Madura, batch 2017. The sample was selected using purposive sampling and obtained 110 students. This study uses multiple linear regression models. The results of this study indicate that student integrity and misuse of information technology have an influence on academic fraud. Meanwhile, Accounting Understanding and Learning Motivation have no effect on academic cheating behavior.Keywords: Student Integrity, Learning Motivation, Accounting Understanding of Information Technology Misuse, Academic Fraud behavior.